2005
DOI: 10.1111/j.0022-202x.2005.23933.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Human Tissue Kallikreins in the Stratum Corneum: Dependence on Age and Gender

Abstract: Human tissue kallikreins are a family of 15 trypsin or chymotrypsin-like secreted serine proteases (hK1-hK15). hK5, hK6, hK7, hK8, and hK13 have been identified in the stratum corneum (SC), stratum granulosum, and skin appendages. It has been reported that hK5 and hK7 degrade desmosomes/corneodesmosomes, suggesting that kallikreins are responsible for desquamation. We report the quantification of hK5, hK6, hK7, hK8, hK10, hK11, hK13, and hK14 in the SC by ELISA and their variation among age groups. The total S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 37 publications
7
98
1
3
Order By: Relevance
“…Up-regulation of hK8 has been reported in human psoriatic lesions (12,13). TPA, an activator of protein kinase C, induces epidermal hyperplasia similar to psoriatic lesion.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Up-regulation of hK8 has been reported in human psoriatic lesions (12,13). TPA, an activator of protein kinase C, induces epidermal hyperplasia similar to psoriatic lesion.…”
Section: Discussionmentioning
confidence: 97%
“…4). Previous reports suggested that both hK6 and hK7 are involved in the pathogenesis of psoriasis (10,13). Cascade reactions of KLKs have been suggested to play a critical role in skin desquamation (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations